Upaya Perbaikan Aktivitas Dan Hasil Belajar Menggunakan Model PBL, Open-Ended Learning, Dan Pair Checks - Rosendi Aditya Suryatama Harahap; Darmiyati (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The problem that occurs is the low activity and learning outcomes in mathematics content. This study aims to describe the activities of educators, analyze activities and learning outcomes. The approach used was a qualitative approach with the type of PTK carried out in three meetings and the subjects studied were fourth grade students at SDN Kelayan Selatan 2 Banjarmasin. The type of data in this discovery is qualitative data obtained from observations of teacher and student activities in the learning process, as well as quantitative data in the form of learning outcomes obtained through written tests. The results showed in this study that the teacher's activities in the first meeting were in the "Good" category, the second meeting achieved the "Good" criteria, and the third meeting achieved the "Very Good" criteria. the activities of students in the first meeting achieved the criteria of "Quite Active" and in the third meeting achieved the criteria of "Very Active". The classical completeness of the learning outcomes at the first meeting was "incomplete", the second meeting was "unfinished", and the third meeting had achieved classical completeness. Based on these results, the researcher concluded that using the PBL, Open-Ended Learning, and Pair Checks models in mathematics content could increase the activity of teachers, students and learning outcomes.